The effects of evening bright light exposure on subsequent morning exercise performance - Thompson, A.; Jones, H.; Marqueze, E.; Gregson, W.; Atkinson, G. (International Journal of Sports Medicine, 2015)
We investigated the effects of evening bright light on the circadian timing of core temperature and morning exercise performance under conditions of high thermal stress. At 20:00 h, 8 males were exposed to a standardised light protocol and thereafter to either polychromatic bright light (2 500 lux at 50 cm, BL) or no light (0 lux, NL) for 30 min. The following morning, intermittent cycling exercise was undertaken followed by a 10 km time-trial in an environmental chamber set to 35°C and 60% relative humidity. Core body temperature was measured throughout. Data were analysed using a within-subjects model and presented as mean±SD. Time of the sleep-trough in core temperature occurred ~1.75 h later following BL (P=0.07). Prior to time-trial, core temperature was 0.27±0.42°C lower in BL (95%CI: -0.02 to 0.57, P=0.07). The time-trial was completed 1.43±0.63 min (0.98-1.87) faster in BL (P=0.001). Post time-trial, intestinal temperature was 38.21±0.56°C (37.84-38.57) in BL compared to 38.64±0.42°C (38.34-38.93) in NL (P=0.10). These data provide the first evidence that a 30-min exposure to bright light prior to sleep can influence exercise performance under hot conditions during the subsequent early morning.